Prevalence and Associated Factors of Depressive Symptoms in Patients with Myasthenia Gravis: A Cross-Sectional Study of Two Tertiary Hospitals in Riyadh, Saudi Arabia - Mohammed H. Alanazy (Behavioural Neurology)
Objectives. This study is aimed at elucidating the prevalence of depression in patients with myasthenia gravis (MG) and examining the risk factors associated with depression. Methods. We evaluated adult patients with MG who were recruited from two tertiary hospitals in the central region (Riyadh) of Saudi Arabia. Data were collected with a two-part standardized questionnaire: the first part included data on sociodemographic and clinical features of MG including disease type and duration, therapies, prednisolone dose, time of the last relapse, previous critical care unit admissions, MG status (controlled, partially controlled, or uncontrolled), and comorbid diseases; the second part included items from the previously validated Arabic version of the Patient Health Questionnaire-9 (PHQ-9). Results. In total, 104/150 (69.3%) patients participated (72 females) with a mean age of 38.0±16.0 years. The mean PHQ-9 score was 7.02±6.1. Among all the participants, 27 (26.0%) patients had depression (PHQ‐9≥10). Multiple logistic regression analysis revealed that uncontrolled MG status (OR=12.31, 95%CI=1.13‐133.8, P=0.04) was the only factor independently associated with depression. Collectively, the prevalence of depression among patients of the primary care clinics (PCC) as reported by 5 previous studies across multiple regions of the country was 15.8%. The odds of depression among MG patients were twofold higher than those among PCC patients (OR=2.05, 95%CI=1.30‐3.22, P=0.002). Conclusions. Approximately a quarter of MG patients have depression. Achieving a minimal manifestation or better MG status may decrease the depression rate in these patients.